Rafik Torosyan - Tadevosyan, Anzhela (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Political repressions of 1930s caused considerable losses in Soviet archaeology. Many experts were repressed, various scientific schools were actually liquidated. In the light of installation of the Short Course of the History of Communist Party any attempts of typologisation and generalization of archaeological materials were announced to be antiscientific. The politics of ‘Thaw’ and national awakening in 1960s put forward a group of young scientists who managed to break the old stereotypes, so defining the further development of archaeology in Armenia. Rafik Torosyan among these archaeologists.